AN ASSESSMENT OF THE EXTENT TO WHICH COMPUTERS HAVE BEEN IMPLEMENTED ON THE CURRICULUM IN MBIRE DISTRICT - MUZENDA, BY DOCTOR VERITY (IJRDO- Journal of Educational Research, 2017)
The aim of the present study is to assess the extent to which computers have been implementedin secondary schools in Mbire district. The population comprised of all the teachers from all thesecondary schools in the district. The sample was made up of 220 respondents comprising of 20heads of schools and 200 teachers randomly selected. The study employed a quantitativemethodology and adopted the descriptive survey design. All the information was collectedthrough a questionnaire. The study revealed that most schools in Mbire district did noteffectively implement computer education. Most of the schools had a critical shortage ofqualified computer teachers and as a result, pupils were taught by teachers who did notunderstand the subject themselves. It was also revealed that heads did not supervise the teachingof computers in a way that supported learning of the subject. The study recommends that theMinistry of Primary and Secondary Education should recruit computer qualified teachers anddeploy them in all secondary schools. Heads should also prioritise the supervision of teaching ofcomputer studies.